Comparative Study of the Essential Oils from Hemidesmus indicus and Decalepis hamiltonii - SREELEKHA, M.; JIROVETZ, L.; SHAFI, P.M. (Asian Journal of Chemistry, 2010)
The essential oils from the dry roots of Decalepis hamiltonii and Hemidesmus indicus were analyzed by GC and GC-MS. Five and seven compounds respectively were identified. 2-Hydroxy-4-methoxybenzaldehyde was found to be the major component in D. hamiltonii (96.29 %) as well as H. indicus (97.89 %). In addition, a comparison of the essential oils from previously investigated fresh and these dry roots of H. indicus was done which showed that 2-hydroxy-4-methoxybenzaldehyde was not lost during drying.